Stature Estimation from Anthropometry of Foot in Adults of Border Areas of Punjab - Megha Rapotra; Jaswinder Kaur (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Stature is one of the various parameters of identification of the individuality of a person. Estimation of stature from various measurements of the body is of value in medicolegal investigations as well as in anthropology. The foot measurements are important in forensic field as they can be used as body height predictors for an individual.The current study deals with developing a regression equation for stature estimation from foot breadth and foot length and to find out the correlation between stature, foot breadth and foot length. Methods: The data was collected from 500 asymptomatic, healthy adults (250 males & 250 females) belonging to border areas of Punjab region of age group ranged between 18-50 years.Results: The correlation between foot length and stature (r= 0.337) was more than foot breadth and stature (r= 0.046) indicating foot length to be a better predictor of stature. Linear regression equations were derived for estimation of stature from foot breadth and foot length.Conclusion: Both foot breadth and foot length showed positive correlation with stature as indicated by the regression coefficient. The results indicate that one can successfully estimate staure from different foot dimensions. The calculated regression formulae show good reliability and applicability of estimate which would be useful for Anthropologists and Forensic Medicine experts.